Highly efficient nanofibrous membranes for low-humidification operation of pem fuel cells - Ripin, Adnan (2015)
The de- and re-regulation of the different network industries is an ongoing process at the global level. As this process unfolds, ever new phenomena emerge, which generally call for more, rather than less regulatory intervention. Yet, the question about the right mixture between market, economic, technical and social regulation remains wide open in all the network industries.